Warunki zastosowania controllingu w zarządzaniu zakładem opieki zdrowotnej - Kogut, Joanna (Controlling as an Concept in Health Care Institutions, 2005)
This article is pointed to present the idea of controlling and to indicate the possibilities of introducing and exploating of it health care institutions.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 236-243